Large-scale phylogeographic study of the cosmopolitan aphid pest Brachycaudus helichrysi reveals host plant associated lineages that evolved in allopatry. (7th September 2016) - Popkin, Megan; Piffaretti, Josephine; Clamens, Anne-Laure; Qiao, Ge-Xia; Chen, Jing; Vitalis, Renaud; Vanlerberghe-Masutti, Flavie; Gupta, Rakesh K.; Lamaari, Malik; Langella, Olivier; Coeur d'acier, Armelle; Jousselin, Emmanuelle
Abstract: Many cosmopolitan plant-eating insect species comprise reproductively isolated population clusters that exhibit contrasting biological (e.g. life cycle) and ecological (e.g. host plant association) characteristics. Phylogeographical studies can untangle such complexities and shed light on the evolutionary forces that drove the divergence between population clusters. In the present study, we investigated the phylogeography of the leaf curl plum aphid ( Brachycaudus helichrysi ), a cosmopolitan pest of Prunus orchards. Using a combination of DNA markers on a set of specimens sampled worldwide, we confirmed the existence of two main lineages (H1 and H2), with differing life cycles. H1 is a sexually reproducing lineage found across the Holarctic on plum trees, whereas H2 consists of globally distributed asexual lineages and few sexual populations that are restricted to West Asia and use peach trees as primary hosts. We further characterized a third lineage (H3), restricted to East Asia, which is associated with apricot trees and Prunus species that are endemic to this region. The divergence of the lineages postdates the speciation of associated Prunus species but precedes their domestication. Our results suggest that, in B. helichrysi, the differentiation between host-specific lineages initially started in geographically isolated populations, which subsequently each adapted to local Prunus species.